Utilization of Cow-dung Ash, Granite Powder and Marble Stone to Enhance Strength of Concrete - Arthika, J; Venkatasubramanian, C; Muthu, D; P Asrani, Neha; Gayathri, R (International Journal of Engineering and Technology, 2018)
The construction industry has been responsible for degrading the environment due to ecological imbalance caused during the extraction and production of building materials. To make this production of construction materials cleaner, the dependency on conventional materials has to be reduced. With this aim, this article presents an experimental study on partial replacement of cement, sand and aggregate by cowdung ash(CDA), granite powder(GP) and marble stone(MS) respectively. For this, four series of mix proportions were prepared to evaluate the compressive strength and the split tensile strength. Replacement ratios of the first, second, third and fourth mixes are (5%CDA, 10%GP, 15%MS), (5%CDA, 15%GP, 30%MS), (10%CDA, 15%GP, 30%MS), (5%CDA, 7.5%GP, 15%MS) respectively. Results revealed that the partial replacement of binders and fillers is effective to enhance compressive and split tensile strength of   concrete. This would enable the construction industry to reduce their dependency on river sand and natural coarse aggregate.
Keywords: Cement; Cowdung ash; Granite powder; Marble stone; Strength.